Leading Sectors among the Provinces of Java Island - Firdaus, Adhy; Hidayatullah, Syarif; Saksana, Joned C.; Susanti, Dwi; Miftahorrozi, Miftahorrozi (Jurnal Manajemen Bisnis dan Keuangan, 2022)
This study aims to analyze the leading sector among provinces of Java Island. To accomplish economic development in a region, the local government often takes part in increasing the GDRP to achieve the people's well-being. It is essential to understand what sectors that could bring the most benefit to the economic agents. This study uses the Location Quotient (LQ) method with the sectoral current price GDRP data. The main result has shown that the provinces of Java Island have their advantage and disadvantage. Most of them excel in the agricultural sector except Jakarta Special Capital Region (SCR). Banten has a better real estate sector than the rest of Java Island, while most services sector has led by Jakarta SCR.